Experiential Marketing, Value, and Service Quality: Impact on RedDoorz Customer Satisfaction - Tirtakusuma, Christian Johny Priyo; Nuvriasari, Audita (LifeSciFi, 2025)
Customer satisfaction is a key indicator of business performance in the hospitality sector, often influenced by marketing strategies, perceived value, and the quality of service. This study aims to investigate the impact of experiential marketing, customer value, and service quality on customer satisfaction. The research employed a quantitative approach, utilizing a non-probability sampling technique, and involved 100 respondents who completed structured questionnaires. Data analysis was carried out through instrument testing, classical assumption testing, and multiple linear regression. The instrument test confirmed that the data used was both valid and reliable. Furthermore, the classical assumption test indicated that the data were normally distributed and met the assumptions of no multicollinearity and no heteroscedasticity, making the regression model appropriate for interpretation. The analysis revealed three key findings: first, experiential marketing has a positive and significant effect on customer satisfaction; second, customer value also has a positive and significant influence on customer satisfaction; and third, service quality has a negative and significant impact on customer satisfaction. In conclusion, the study demonstrates that both marketing experiences and perceived value strongly shape customer satisfaction, while poor service quality can reduce satisfaction levels.